Biogenic ZnO Nanoparticles Derived from Garcinia gummi-gutta Leaves: Synthesis, Characterization and its Multifaceted Applications - Kurian, J.T.; Joseph, K.S. (Asian Journal of Chemistry, 2024)
The current study focused on the bioreduction synthesis of ZnO nanoparticles using Garcinia gummi-gutta leaf extracts. The UV-vis analysis of the nanoparticles has reported the formation of an SPR peak at 379 nm. The functional groups taking part in the reduction reaction were analyzed using the FTIR technique and the average crystalline size of ZnO nanoparticles were found to be 22.27 nm from XRD measurements. The SEM and TEM images revealed the hexagonal shape of the nanoparticles with an average size 72.78 nm and 71.91 nm, respectively. Further, the synthesized nanoparticles were reported to be efficient degradation reactive textile dyes. The photodegradation results reported 92-100% degradation of the reactive dyes within 80-320 min. The antibacterial efficacy of the nanoparticles was investigated and the MIC of the nanoparticles was found to be 100 µg/mL. The synthesized ZnO nanoparticles have exhibited significant cytotoxic effects on the MCF and HEP-G2 cell lines.